The cognition of civil servants and citizens concerning policy resource allocation in Kaohsiung City in Taiwan - Yu-tien Huang; Ming-shen Wang (International Journal of Management, Economics and Social Sciences (IJMESS), 2014)
Kaohsiung City is a special municipality in Southern Taiwan. The difference between northern and southern cities in terms of public investments, industrial structures, and social perspectives has been a problem in Taiwan because talented people keep moving from the south to the north. The difference in cognition of government's allocation of policy resources between professional civil servants and the general public demonstrates the conflict between "public opinion" and "professionalism". This study adopted the social judgment theory (SJT) to examine the cognition of individuals affected by policy resource allocation regarding the allocation of policy resources made by the Government of Kaohsiung City. The SJT is applicable to real-world circumstances in the field of judgment and analysis. The research result indicated that the affected individuals were concerned that the government lost its focus when allocating policy resources. Obscure schemes and plans for policymaking and election-oriented decision making significantly impact government allocation of policy resources. The essential problem of policy resource allocation in Kaohsiung City is that although the supply of resources is higher than the demand, the types of resources do not meet the requirements of the demand.
Keywords: D73; G18; I38; L52; 330; Civil servant; Cognitive Psychology; Policy Resource; Resource Allocation; Social Judgment Theory